2010
DOI: 10.1142/9789814293488_0008
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft Observations of Tropical Cyclones

Abstract: Nine different types of aircraft are currently in use to observe tropical cyclones and their environments for operations and research. The following is a description of those aircraft, their instrumentation, and the field programs with which they have been involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Though aircrafts can provide precise information about the development, intensity change, and track of a TC, these observations are mainly available in the Atlantic basin (Aberson et al, 2010;Gray, Neumann, & Tsui, 1991;Martin & Gray, 1993).…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though aircrafts can provide precise information about the development, intensity change, and track of a TC, these observations are mainly available in the Atlantic basin (Aberson et al, 2010;Gray, Neumann, & Tsui, 1991;Martin & Gray, 1993).…”
Section: Data Collectionmentioning
confidence: 99%
“…Even with multiple forecasting techniques in operation, TC forecasting centers are still struggling to handle this difficulty. Considering the operational forecasting techniques' limitations in TC intensity forecasting (Aberson et al, 2010;DeMaria et al, 2007;Rogers et al, 2006), as well as the inefficiencies of the current cyclone early warning system in Bangladesh (Akhand, 2003;U. Haque et al, 2012), new techniques, equally effective in TC track and intensity forecasting need to be explored.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Supplementary dropsonde data gathered during tropical cyclone reconnaissance missions and ingested into operational numerical weather prediction (NWP) systems have, in most cases, resulted in reduced tropical cyclone track forecast errors. In particular, data gathered in the hurricane environment have provided improved depiction of hurricane steering winds and the large-scale troughs and ridges that highly influence hurricane tracks (e.g., Aberson et al 2010;Majumdar et al 2013;Brennan et al 2015). Moreover, for dropsondes deployed in the vicinity of extratropical and tropical cyclones in midlatitudes during the North Atlantic Waveguide and Downstream Impact Experiment (NAWDEX), Schäfler et al (2018) and Schindler et al (2020) have shown positive downstream impact.…”
Section: Introductionmentioning
confidence: 99%
“…In extensive studies prior to this period, TCs were examined with aircraft, but, with limited exception, those studies will not be covered here. The interested reader is referred to [19,20] for a comprehensive assessment of these earlier studies that documented TC structure and intensity from aircraft observations. Intensity change, as defined here, includes a range of intensification rates, including the RI of tropical storms to major hurricanes; slower (but still substantial) intensification of TCs with initial intensities ranging from tropical depressions to hurricane strength; the organization of tropical depressions into tropical storms that subsequently undergo RI; and the formation of tropical depressions from disorganized tropical cloud clusters.…”
Section: Introductionmentioning
confidence: 99%